The Relationship between Vocabulary Mastery and Reading Interest with Speaking Skills for Elementary School Students - Sriyanti, Sriyanti; Surastina, Surastina; Istiara, Febriyantina (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2018)
This study aims to describe the relationship between reading interest and vocabulary mastery with the speaking skills of the sixth grade students of SDN 13 Gedung Tataan Pesawaran. This research was conducted due to the fact that speaking skills and vocabulary mastery, as well as reading interest need to be developed. Researchers use the correlational method. The technique used in collecting research data is a questionnaire and a test. Testing the research hypothesis using correlation coefficient test, product moment and multiple correlation. Previously, analysis prerequisite tests were carried out, namely data normality and linearity tests. Based on the results of the study it can be concluded that, (1) there is a positive and significant relationship between interest in reading and speaking skills, indicated by a correlation coefficient of 0.766 and a coefficient of determination (r2) of 0.587 or 58.7%, (2) there is a significant relationship positive and significant relationship between vocabulary mastery and speaking skills as shown by the correlation coefficient of 0.662 and the coefficient of determination (r2) of 0.438 or 43.8%, (3) there is a positive and significant relationship between interest in reading and vocabulary mastery with speaking skills indicated by a correlation coefficient of 0.804 and a coefficient of determination (r2) of 0.646 or 64.6%.